Case Study of Successfully Staged Acid Fracturing on the Ultra-Deep Horizontal Well for the Qixia Fm HTHP Tight Carbonate Gas Reservoir in China - Liu, Fei; Fan, Yu; Li, Li; Li, Jinsui; Chen, Yan; Lv, Zefei; He, Tingting (Frontiers in Energy Research, 2022)
The lower Permian Qixia formation gas reservoir is characterized by ultra-deep buried, high temperature and high pressure (HTHP), low porosity and permeability, ultra-high closure pressure, and thin thickness in the western Sichuan Basin, China. Acid fracturing has been adopted as the main well stimulation technology. The average test production of the acid-fractured vertical well was 46 × 104 m3/d. The horizontal well with staged acid fracturing is considered a reliable measure to enhance gas production. However, the staged acid fracturing on the ultra-deep horizontal well has been challenged. The reaction rates of conventional, self-diverting, and gelled acid and the acid-etched fracture conductivity experiments under HTHP are measured to optimize the acid fracturing technique. The reaction rate of gelled acid with Qixia Fm limy dolomite at 150°C is 3.4–6.7 times faster than that with dolomite and similar to that with limestone. The gelled acid with better retardation and friction reduction performance is selected as the main acid to increase the effective acid-etched fracture length. The acid-etched fracture conductivity can be greatly enhanced by using gelled acid, increasing acid volume, and closed fracture acidizing (CFA) under a closure stress of 50 MPa. Moreover, the feasibility of staged acid fracturing for ultra-deep horizontal wells is discussed. The first stage is assembled by fracturing sleeve, spared ball drop sleeve, and circulating valve to ensure activation of the fracturing channel. The tested production is significantly enhanced with temporary plugging and open-hole packer and sliding sleeve staged acid fracturing.